Junctures in Women's Leadership: Social Movements - Bernstein, Alison R., 1947-2016; Trigg, Mary K., 1955- (Book collections on Project MUSE., 2016)
The case studies in Junctures in Women's Leadership: Social Movements introduce readers to twelve women from across the globe who have spearheaded a wide array of social movements, from gender equality to environmental justice. Examining how these women made sacrifices, asked critical questions, challenged injustice, and exhibited the will to act in the face of harsh criticism, these case studies also provide a unique window into the ways that women leaders make decisions at moments of struggle and historical change.